Outpatient hysteroscopy. Issue 1 (January 2016) - Graham, Anna; Datta, Shreelata
Abstract: The face of gynaecology is changing, and as it develops into a mainly ambulatory speciality. Surgical procedures previously carried out as day case surgery or as in patient are now increasingly performed in the outpatient setting. This is true of hysteroscopic procedures that were traditionally theatre based in hospital, but are now are performed in the outpatient setting as first line in many centres. Crucially this has been shown to be both cost effective and acceptable to patients. This review will provide an overview of the indications, current guidelines and best practice techniques for clinicians performing both diagnostic and therapeutic outpatient hysteroscopies.